THE CRITICAL THINKING SKILLS OF BIOLOGY TEACHER CANDIDATES TOWARD THE ETHICAL ISSUES - Maryuningsih, Yuyun; Hidayat, Topik; Riandi, R.; Rustaman, Nuryani Y. (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
The critical thinking skills are needed by biology teacher candidates to deal with the nowadays ethical issues arisen among society. The aim of this research was to observe the critical thinking skills of biology teacher candidates toward the ethical issues especially in genetic field through online discussion. The subjects of this experimental research were 104 biology teacher candidates who took the Genetics Course in an institution in West Java.  The subject were devided into three groups consisted of two experimental groups and one control group which conducted online discussion by using Gen-21cs application. The experimental groups discussed the topics given by the both instructor and students, while the control group only discussed the topics given by the instructor. The topics discussed were cell cloning, Genetically Engineered Products, stemcell and inbreeding. The online discussions have been done for four weeks. The biology teacher candidate responses were measured using the critica thinking measurement developed by Facione.The critical thinking scores gained were analyzed using descriptive statistic in term of mean. The results showed that the critical thinking skills of the biology teacher candidates tended to increase in each discussion sessions. Online discussion can be used to ensure the other thinking skills.